Ketentuan Pidana dalam Undang-Undang Perlindungan Data Pribadi: Studi Perbandingan Hukum antara Indonesia dan Singapura - Dian Purwaningrum Soemitro; Muhammad Arvin Wicaksono; Nur Aini Putri (CV. Social Politic Genius (SIGn), 2023)
This study aims to compare the penal provisions between the PDPA and Law Number 27 of 2022. This study uses normative legal research with the statute and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show a striking difference between the PDPA and Law Number 27 of 2022 concerning penal provisions related to offenses of personal data protection. The PDPA portrays a more moderate approach by establishing relatively lighter imprisonment and fines. In contrast, Law Number 27 of 2022 illustrates a stricter approach with more severe imprisonment, fines, and additional punishments. Singapore leans towards prevention and education, while Indonesia places a high priority on law enforcement. Nonetheless, both approaches ultimately aim to protect their citizens’ personal data. Therefore, it recommended that the relevant authorities in both Singapore and Indonesia continually evaluate and adapt their legal frameworks to safeguard personal data effectively. Singapore could consider stricter penalties to discourage offenses while maintaining its focus on education and prevention. On the other hand, while Indonesia’s commitment to law enforcement is commendable, it could also benefit from incorporating preventive measures and public education to promote understanding and voluntary compliance. Collaborative efforts between the two countries can facilitate continual enhancements in personal data protection within their respective jurisdictions.